Potential Use of Municipal Solid Waste Pile in Segawe Landfill (Tulungagung Regency, Indonesia) as Raw Material for Refuse Derived Fuel - Haruko, Dalila Putri; Trihadiningrum, Yulinah; Wilujeng, Susi Agustina; Radita, Deqi Rizkivia; Bagastyo, Arseto Yekti (Geomatics and Environmental Engineering, 2024)
The Segawe municipal solid waste (SW) landfill in Tulungagung Regency, Indonesia, has currently exceeded its capacity. This study aimed to determine the potential use of dumped SW at the landfill as raw material for the production of refuse derived fuel (RDF). Buried SW samples were collected at a passive zone of the landfill in six locations. The samples were sieved using 10 and 30 mm mesh sieves. A composition analysis was conducted following the ASTM D5231-92 method to sample fractions of greater than 30 mm size. The density was measured according to the weight and volume. The moisture and volatile matter contents were analyzed using the ASTM D2216-10 and D3175-07 methods, respectively. The calorific value was measured using a Parr C3000 bomb calorimeter following the ASTM D5865 method. The buried SW composition was dominated by a fraction size that was greater than 30 mm (79.4%). This fraction was dominantly composed of plastics (71.2%) and had average volatile matter and calorific values which met RDF criteria as a fuel. However, the ash and moisture contents exceeded the standards and, therefore, required appropriate treatments before their applications.